THE EVOLUTION AND GROWTH OF THE COFFEE INDUSTRY IN INDONESIA: FROM COLONIAL HISTORY TO MODERN CAFES - Wibowo, Bambang Sri; Atmajawati, Yayah; Ali, Umar (Transpublika Publisher, 2024)
Coffee has stories that are always interesting to hear from ancient times to the present (Angeloni, G., L. Guerrini, P. Masella, M. Bellumori, S. Daluiso, A. Parenti, and M. Innocenti. 2019a). This drink has fans all over the world with a variety of interesting processing methods and interesting flavors too. Coffee plants are also spread in many countries around the world. In Indonesia, various types of coffee plants are widely planted in several highland areas. A simple processing process in order to maintain the original taste and aroma of coffee is always sought by many farmers and coffee entrepreneurs in many regions. Stories about coffee in the modern era will be presented in qualitative form in this article. Currently, coffee has become a product that is sought after by many fans in places that provide it in different settings. So, if you look closely at this drink, it can also sell the atmosphere of the place that sells it as a companion product. Many shops, cafes and restaurants and even food trucks